2020
DOI: 10.1039/d0ma00008f
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of h-BN into c-BN for tuning optoelectronic properties

Abstract: Phase pure c-BN and mixed phased h-BN and c-BN films on c-sapphire were fabricated by pulsed laser annealing for tuning optical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Detailed description of the characterization techniques, i.e., scanning electron microscopy (SEM), electron backscattering diffraction (EBSD), Raman spectroscopy, X-ray diffraction (XRD), and electrical measurements are described elsewhere. 21 2.2. SIMS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed description of the characterization techniques, i.e., scanning electron microscopy (SEM), electron backscattering diffraction (EBSD), Raman spectroscopy, X-ray diffraction (XRD), and electrical measurements are described elsewhere. 21 2.2. SIMS.…”
Section: Methodsmentioning
confidence: 99%
“…To convert h-BN into c-BN, we have used a pulsed ArF laser (wavelength = 193 nm, pulse duration = 20 ns) and irradiated the C-doped h-BN films in air at energy densities in between 0.7 and 0.75 J cm –2 . Detailed description of the characterization techniques, i.e., scanning electron microscopy (SEM), electron backscattering diffraction (EBSD), Raman spectroscopy, X-ray diffraction (XRD), and electrical measurements are described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…It was found that the CS94 model describes the experimental data better. This observation might be further examined at high temperatures (e.g., T > 1500 K) using some novel experimental techniques, such as the pulsed laser annealing technique with superfast T -quenching capability [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cubic boron nitride (c-BN) has a high hardness, good high-temperature chemical stability, corrosion resistance, and oxidation resistance [1][2][3][4][5][6][7]. It does not react with metals such as iron, cobalt, and nickel at high temperatures, making it the preferred material for processing ferrous metals [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It does not react with metals such as iron, cobalt, and nickel at high temperatures, making it the preferred material for processing ferrous metals [1][2][3][4]. In addition, c-BN, as a third-generation semiconductor material, has excellent electrical and optical properties such as an ultra-wideband gap, high thermal conductivity, and a low dielectric constant [5][6][7]. It has broad application prospects in fields such as high-power electronics, deep ultraviolet optoelectronics, and quantum communication.…”
Section: Introductionmentioning
confidence: 99%